2022
DOI: 10.1039/d2sc05143e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine extraction from organofluorine molecules to make fluorinated clusters in yttrium MOFs

Abstract: A new rare earth based two-dimensional coordination network and a three-dimensional metal-organic framework (MOF) have been synthesized using bicinchoninic acid (BCA) and yttrium(III) ions. Yttrium dimer nodes are formed in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…1 MOFs are used in a variety of applications such as biomedicine, 2-6 catalysis, 7,8 sensors, [9][10][11] conductors, [12][13][14][15] gas storage and separations. [16][17][18][19][20] The capture and storage of CO 2 is a growing area of research. CO 2 gas has been acknowledged as a major contributor to global warming since the 1850s, when the first IR heat absorbance experiments of atmospheric gases were published.…”
Section: Introductionmentioning
confidence: 99%
“…1 MOFs are used in a variety of applications such as biomedicine, 2-6 catalysis, 7,8 sensors, [9][10][11] conductors, [12][13][14][15] gas storage and separations. [16][17][18][19][20] The capture and storage of CO 2 is a growing area of research. CO 2 gas has been acknowledged as a major contributor to global warming since the 1850s, when the first IR heat absorbance experiments of atmospheric gases were published.…”
Section: Introductionmentioning
confidence: 99%
“…The popular modulator, 2-fluorobenzoic acid (2-fba), has been widely used to create lanthanide MOFs containing nona-, , hexa-, and triclusters . The formation of such clusters can increase the chemical and thermal stability of the Ln MOFs. , Recently, it was reported that lanthanides react with the 2-fba and extract fluoride, , which becomes incorporated into the MOF structures as fluoro-bridges between the metal ions. For example, Ho-UiO-66 contains a fluoro-bridged hexanuclear cluster when prepared using 2-fba …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In this process, functional groups worked as catchers for pollutants, and the pores/cavities acted as containers for stabilizing the adsorbed pollutants to avoid desorption. [14][15][16] MOF materials have achieved excellent performance in pollutant removal, especially in the improvement of the selectivity by modifying the adsorption sites, [17][18][19][20] while the difficulty and limited accessibility to the active sites buried in the framework of bulky MOFs made a significant discount on their adsorption performances, including adsorption selectivity and uptake capacities. 21 The abovementioned drawbacks may be solved by twodimensional (2D) MOF nanosheets, highly open structures with sufficiently exposed surfaces and accessible active sites.…”
Section: Introductionmentioning
confidence: 99%